A comment on "Novel scavenger removal trials increase wind turbine‐caused avian fatality estimates"1. Issue 2 (7th January 2013) - Huso, Manuela M.P.; Erickson, Wallace P.
Abstract: In a recent paper, Smallwood et al. (2010) conducted a study to compare their "novel" approach to conducting carcass removal trials with what they term the "conventional" approach and to evaluate the effects of the different methods on estimated avian fatality at a wind power facility in California. A quick glance at Table 3 that succinctly summarizes their results and provides estimated fatality rates and 80% confidence intervals calculated using the 2 methods reveals a surprising result. The confidence intervals of all of their estimates and most of the conventional estimates extend below 0. These results imply that wind turbines may have the capacity to create live birds. But a more likely interpretation is that a serious error occurred in the calculation of either the average fatality rate or its standard error or both. Further evaluation of their methods reveals that the scientific basis for concluding that "many estimates of scavenger removal rates prior to [their] study were likely biased low due to scavenger swamping" and "previously reported estimates of avian fatality rates … should be adjusted upwards" was not evident in their analysis and results. Their comparison to conventional approaches was not applicable, their statistical models were questionable, and the conclusions they drew were unsupported. © 2013 The Wildlife Society.